The impact of Zimbabwe’s drought policy on Sontala rural community in Matabeleland South province - Dube, Carolina (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Geography and Environmental Studies))--Stellenbosch University, 2008.